2020
DOI: 10.1101/2020.09.08.288381
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Characterization of SOX2, OCT4 and NANOG in ovarian cancer tumor-initiating cells

Abstract: Identification of tumor initiating cells (TICs) has traditionally relied on expression of surface markers such as CD133, CD44, and CD117 and enzymes such as aldehyde dehydrogenase (ALDH). Unfortunately, these markers are often cell type specific and not reproducible across patient samples. A more reliable indication of TICs may include elevated expression of stem cell transcription factors such as SOX2, OCT4, and NANOG that function to support long-term self-renewal, multipotency, and quiescence. RNA-sequencin… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…Further studies are required to confirm these theories. In this context, Robinson et al recently reported a stronger role for SOX2 compared to OCT4 or Nanog for tumor relapse potential following chemotherapy in ovarian cancer patients and that HGSC cell lines displayed greater chemoresistance and increased expression of SOX2 , OCT4 , and Nanog when grown in 3D conditions compared to 2D [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Further studies are required to confirm these theories. In this context, Robinson et al recently reported a stronger role for SOX2 compared to OCT4 or Nanog for tumor relapse potential following chemotherapy in ovarian cancer patients and that HGSC cell lines displayed greater chemoresistance and increased expression of SOX2 , OCT4 , and Nanog when grown in 3D conditions compared to 2D [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…CD117, in combination with CD44, has been used to identify CSCs [ 30 ]. CD117+ ovarian cancer cells overexpress SOX2, octamer-binding transcription factor 4 (OCT4), and NANOG, which are CSC markers involved in stemness and chemoresistance [ 45 ]. CD117 overexpression in ovarian CSCs elevates tumor-initiating capacity and chemoresistance against cisplatin/paclitaxel via the induction of the Wnt/beta-catenin-ATP–Binding Cassette Subfamily G Member 2 (ABCG2) axis [ 46 ].…”
Section: Cell Surface Markers Of Ovarian Cscsmentioning
confidence: 99%
“…In addition, low-dose cisplatin treatment induces stemness in ovarian cancer cells [ 99 ]. OCT4, SOX2, and NANOG are significantly overexpressed in high-grade serous ovarian cancer cell lines cultured under 3D culture conditions, and CD117+ or ALDH+/CD133+ cells exhibit elevated expression of stemness genes [ 45 ]. SOX2, but not OCT4 or NANOG, has been implicated in early tumor initiation and plays a more substantial role in tumor relapse in ovarian cancer patients.…”
Section: Intracellular Markers Of Ovarian Cscsmentioning
confidence: 99%
See 1 more Smart Citation